BREAKING THE MOLD: FOSTERING A CULTURE OF RESEARCH IN PAKISTAN - Sarwar, Iram (Journal of Ayub Medical College Abbottabad, 2024)
Pakistan is a developing country in South Asia which has specific cultural, religious, economic, and geographical challenges which need to be addressed concomitantly when one speaks about research culture in Pakistan. Pakistan is suffering from a scarcity of domestic, indigenous research which could help identify psychosocial epidemiological patterns and viz a viz, the development of culturally appropriate policies and interventions. The purpose of this editorial is to identify barriers in developing result culture in Pakistan and its solutions. It is difficult to recognize a uniformly satisfying definition of a culture of research. To provide a broad and useful conception Teresa Marchant, characterizes culture as a system of widely shared and strongly held values. This would make a culture of research a system that places great value on conducting and communicating scholarly research